The relationship between reaction time, eye-hand coordination with visual field in elite tennis tennis players - Asar, S.; Ezabadi, R. R.; Baghini, A. S.; Maleksabet, N. (Asian Journal of Sports Medicine, 2022)
The current study investigates the relationship between simple reaction time, choice reaction time, and eye-hand coordination with peripheral vision in elite female table tennis players. Ten female table tennis players of the Iranian national team with a mean age of 19.7 ± 5.964, in the 18th Asian Games of 2018, Jakarta, participated via convenience sampling. The visual field was evaluated with the Humphrey automated perimetry. Choice and simple reaction time were assessed using Deary-Liewald reaction time tester software. In order to measure eye-hand coordination, the manual test of alternate-hand wall toss was used. Data were analyzed in statistical package for the social sciences using Pearson`s correlation. The results show that there was no significant relationship between simple and choice reaction time with peripheral vision in the left and right eyes. Also, results show that there was no significant relationship between eye-hand coordination with peripheral vision in the left and right eyes (P = 0.05). The findings of this study show that experts in an activity visually searched their environment and located essential information more effectively and efficiently than novices. Therefore, we know that this visual feature is more a function of expertise than visual acuity.